An Empirical Shear Model of Interface Between the Loess and Hipparion Red Clay in a Loess Landslide - Zhu, Yanbo; Miao, Shuaisheng; Li, Hongfei; Han, Yutao; Lan, Hengxing (Frontiers in Earth Science, 2022)
Quaternary loess is widely distributed over the Tertiary Hipparion red clay on the Loess Plateau of China. Large-scale loess landslides often occur along the weak contact interface between these two sediment materials. To investigate the failure mode and shear strength characteristics of the loess-Hipparion red clay contact interface, a series of shearing experiments were performed on interface specimens using purpose-built shear equipment. In this paper, the relationship between shear strength and interface morphology is discussed, and an empirical shear model of interface is proposed based on the experimental results and theoretical work. The results indicate that discontinuities between the loess and the Hipparion red clay reduce the shear strength of specimens significantly. The contribution of the contact interface to shear performance including failure mode, shear deformation and shear strength varies with the interface morphology and the applied normal stress. With low interface roughness or normal stress, sliding failure is likely to occur. With increasing interface roughness and normal stress, the peak strength increases rapidly. With further increase in the interface roughness and normal stress, the increment of peak strength decreases gradually as the failure mode transitions from sliding mode to cutoff mode. A staged shear model that takes the failure mode into consideration is developed to express the nonlinear change in the interface shear strength. The shear model’s capability is validated by comparing model estimates with experimental data. This work improves our understanding of shear mechanisms and the importance of considering the effects of interfacial properties in the mechanical behavior of contact interfaces.